Early Functional Outcome of Ceramic on Ceramic Total Hip Replacement Using a 36 mm Diameter Femoral Head: An Advance Study - Sonu Mehta; Deepak Aher; Shoaib Sheikh; Devendra Patkar (Highlights on Medicine and Medical Research Vol. 13, 2021)
At a tertiary care hospital, 30 patients with diseased hips were treated with uncemented total hip replacement with a 36 mm femur head and a ceramic on ceramic bearing. The study included patients aged 30 and up, with the oldest patient being 75 years old. The most common reason for surgery was secondary osteoarthritis of the hip joint caused by femoral head avascular necrosis (21 patients). Other causes were primary osteoarthritis of the hip(3 patients), intermediate stage of avascular necrosis of femur head which had not progressed to the stage of osteoarthritis (2 patients), osteoarthritis post old history of trauma(2 patients), osteoarthritis post healed tuberculosis of the hip(1 patient), and ankylosing spondylitis (1 patient). The patient was given a complete clinical and radiological assessment. Eight hours following surgery, all patients were instructed to perform isometric quadriceps activity. On the first post-operative day, patients were instructed to sit up and given knee bending exercises. On the first post-operative day, patients were encouraged to stand and walk non-weight bearing or partially weight bearing as tolerated. On the 12th post-operative day, the sutures were removed. The average length of stay in the hospital was five days. The follow-up period lasted for 18 months. After 12 and 18 months post operation, patients were evaluated using the modified Harris Hip Score and the WOMAC score. All of the patients were followed up on a regular basis, and none of them were missed. During the research period, there were no complications. The mean Modified Harris Hip Score increased significantly from 26.6 pre operatively to 89.3 post operatively at 12 months and 90.0 at 18 months. The mean WOMAC score has decreased significantly from 70.5 pre operatively to 14.8 post operatively at 12 months and 14.2 at 18 months. This demonstrates that an uncemented total hip arthroplasty with a 36 mm femur head and a ceramic on ceramic bearing can produce outstanding results. Total hip replacement is a permanent method of relieving pain in the hip due to various conditions.